2017
DOI: 10.15406/jnmr.2017.05.00136
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide for Biomedical Applications

Abstract: Graphene oxide (GO) is one of the most promising functional materials used in various applications like energy storage (batteries and supercapacitors) sensors, photocatalysis, electronics and in biomedicine. The last 10 years literature on GO for biomedical applications revealed and confirmed the scope of its potential capabilities as biomaterial. GO alone and its modified form with different materials (surface functionalization, immobilization of nanoparticles and composite formation) also proved as a multifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“… Orthopedic implant coating materials include; Calcium phosphate-based biocompatible materials, graphene oxide and other polymers [2]. Graphene oxide is gaining attention in bio-compatible materials industry targeting medical applications [3].  Previous experimental studies have shown that GO coatings might be a good candidate as a coating material for orthopedic implants [4].…”
Section: Introductionmentioning
confidence: 99%
“… Orthopedic implant coating materials include; Calcium phosphate-based biocompatible materials, graphene oxide and other polymers [2]. Graphene oxide is gaining attention in bio-compatible materials industry targeting medical applications [3].  Previous experimental studies have shown that GO coatings might be a good candidate as a coating material for orthopedic implants [4].…”
Section: Introductionmentioning
confidence: 99%
“…106,107 GO possesses physicochemical properties and biocompatibility due to its unique structure, which is a graphene basal plane attached with functional groups like hydroxyl (OH) and carboxylic (COOH), which leads to further functionalization and conjugation or immobilization of other nanoparticles on its surface. [108][109][110][111][112] In addition, the GO surface's morphology, shape, size, and functional groups stimulate biological activity and may even improve cell-cell interactions. 113 Because GO has excellent surface functionality and is rich in oxygen-containing groups, it can be easily modified with other materials, improving solubility, selectivity, and biocompatibility.…”
mentioning
confidence: 99%
“…103,113 Interestingly, because GO is photoluminescent and permeable to cell membranes, it can be used in drug delivery and gene delivery. 117 As a result, GO has been predominantly used in biomedical applications such as tissue engineering, cancer therapy, drug delivery, gene delivery, and biosensing, 108,[118][119][120] as illustrated in Figure 2.…”
mentioning
confidence: 99%